Public Opinion Analysis of Big Data Based on Machine Learning. Issue 2 (August 2019) - Chen, Xuegang; Fan, Hongbin; Duan, Sheng; Wang, Luda; Zhang, Jialu
Abstract: Network public opinions can be regarded as a collection of network comments, that is, a network comment can be regarded as the basic unit of network public opinion, based on this, network comment can be divided into spam comment, subjective comment and objective comment, we combine feature extraction method with machine learning method, machine learning method includes naive bayes and threshold delineation, and classify different types of network comments. By a large number of experiments, we have proved that the classifying accuracy of network comments is high, and the machine learning method can reduce the noise of text classification.